1999
DOI: 10.1038/sj.bjc.6690476
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of neomycin, faecal neutral and acid sterols with colon carcinogenesis in rats

Abstract: Summary High fat diets have been implicated in incidence of colon cancer both in epidemiological and animal studies. Present investigation deals with the incidence, location and numbers of large and small bowel tumours induced by 1,2-dimethyl hydrazine (DMH) in rats fed high fat diets and neomycin. Neomycin was used to modify the faecal sterol metabolism and the relationship of the high fat diet and faecal neutral and acid sterols to the large bowel tumorigenesis was evaluated. DMH administered rats were fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In this sense, it has been established that secondary metabolites of fecal steroids produced by the gut microbiota may promote health or favor disease development depending on the quantity and type produced. Specifically, increased concentrations of secondary bile acids (BAs) and cholesterol microbial metabolites in feces are involved in colorectal carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it has been established that secondary metabolites of fecal steroids produced by the gut microbiota may promote health or favor disease development depending on the quantity and type produced. Specifically, increased concentrations of secondary bile acids (BAs) and cholesterol microbial metabolites in feces are involved in colorectal carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas unmetabolised cholesterol is subjected to extensive enterohepatic circulation, coprostanol is poorly absorbable and excreted in the faeces [4]. However, epidemiological 0378 studies have revealed that high-risk populations for colon cancer have an increased number of total anaerobes and enhanced metabolism of neutral sterols [7], and coprostanol is thought to be associated with colorectal carcinogenesis [8,9]. However, epidemiological 0378 studies have revealed that high-risk populations for colon cancer have an increased number of total anaerobes and enhanced metabolism of neutral sterols [7], and coprostanol is thought to be associated with colorectal carcinogenesis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The end‐product is mainly the fully saturated and poorly absorbable coprostanol (5β‐cholestan‐3β‐ol) whose formation would facilitate the elimination of cholesterol from the body [1,2], and would therefore decrease the risk of cardiovascular diseases [2]. The ambiguity of coprostanol in a clinical perspective must however be pointed out, since this metabolite could be associated with colorectal carcinogenesis [3–5]. Interestingly, the efficiency of microbial conversion of cholesterol to coprostanol among human populations has been found to be bimodal, with a vast majority of high transformers and a minority of low‐to‐inefficient transformers [6,7].…”
Section: Introductionmentioning
confidence: 99%